Global respiratory tumor mortality correlation study with economic level, 2000–2019 - Mingjie Wang; Mingjie Wang; Zhiyuan Chen (Frontiers in Public Health)
ObjectiveThe study aimed to investigate the relationship between global tracheobronchial lung cancer mortality rates and economic levels and assess the associated regional economic burden. Understanding these associations is crucial for global health resource allocation, informing cancer prevention and control strategies, and providing data to support the development of lung cancer and economic policies worldwide.MethodsWe analyzed respiratory cancer mortality data (International Classification of Diseases (ICD)-10 codes C33-C34) obtained from the World Health Organization (WHO) Mortality Database (2000–2019). Age-standardized mortality rates (ASMRs) were calculated to describe the spatiotemporal distribution characteristics. Non-parametric comparisons (Wilcoxon rank-sum test) were performed to assess gender differences in mortality. Spearman’s partial rank correlation analysis was performed to evaluate the association between national income levels (World Bank classification) and disease mortality.ResultsThe core cohort included 50 countries with sufficient data. The global mean ASMR for respiratory cancers showed a decreasing trend from 2000 to 2019. Countries included in the Global Respiratory Tumor Mortality Registry System (GRTMRS) were predominantly high-income (68%) and European (52%). A significant positive correlation was observed between income levels and respiratory cancer mortality (Spearman’s ρ = 0.422, p < 0.001). ASMRs were consistently and significantly higher among male individuals than female individuals (Wilcoxon rank-sum test, p < 0.001).ConclusionBetween 2000 and 2019, global tracheobronchial lung cancer mortality appeared to be positively correlated with national economic level, particularly in high- and middle-income countries. Age-standardized mortality rates were significantly higher in male individuals than in female individuals. Paradoxically, these findings suggest that increasing economic development may be associated with elevated respiratory cancer mortality rates, emphasizing the critical need for balanced prevention strategies tailored to both high- and low-income settings.